2020
DOI: 10.1038/s41587-020-0673-2
|View full text |Cite
|
Sign up to set email alerts
|

Epineural optogenetic activation of nociceptors initiates and amplifies inflammation

Abstract: Activation of nociceptor sensory neurons by noxious stimuli both triggers pain and increases capillary permeability and blood flow to produce neurogenic inflammation 1 , 2 , but whether nociceptors also interact with the immune system remains poorly understood. Here we report a neurotechnology for selective epineural optogenetic neuromodulation of nociceptors and demonstrate that nociceptor activation drives both protective pain behavior and inflammation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 42 publications
0
53
0
Order By: Relevance
“…Similarly, recent evidence points to a role of lung nociceptor neurons in initiating downstream Th2 cell activation and subsequent allergen-induced inflammation (81). Another recent study using optogenetic activation of nociceptors in naïve mice demonstrated that levels of dDCs and gd, ab T cells and DETCs increased in the skin after optogenetic stimulation (82). Further, optogenetic nociceptor stimulation in mice treated with complete Freund's adjuvant induced significant additional increases in the numbers of gd and ab T cells in the inflamed skin indicating that antidromic nociceptor activation alone is sufficient to induce and potentiate inflammation (82).…”
Section: Immune Cell Regulation By Sensory Neurons In the Skinmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, recent evidence points to a role of lung nociceptor neurons in initiating downstream Th2 cell activation and subsequent allergen-induced inflammation (81). Another recent study using optogenetic activation of nociceptors in naïve mice demonstrated that levels of dDCs and gd, ab T cells and DETCs increased in the skin after optogenetic stimulation (82). Further, optogenetic nociceptor stimulation in mice treated with complete Freund's adjuvant induced significant additional increases in the numbers of gd and ab T cells in the inflamed skin indicating that antidromic nociceptor activation alone is sufficient to induce and potentiate inflammation (82).…”
Section: Immune Cell Regulation By Sensory Neurons In the Skinmentioning
confidence: 94%
“…Another recent study using optogenetic activation of nociceptors in naïve mice demonstrated that levels of dDCs and gd, ab T cells and DETCs increased in the skin after optogenetic stimulation (82). Further, optogenetic nociceptor stimulation in mice treated with complete Freund's adjuvant induced significant additional increases in the numbers of gd and ab T cells in the inflamed skin indicating that antidromic nociceptor activation alone is sufficient to induce and potentiate inflammation (82). This study further illustrates the strong links between sensory neurons and immune cells in the skin.…”
Section: Immune Cell Regulation By Sensory Neurons In the Skinmentioning
confidence: 99%
“…The targeted mouse genetic (NaV1.8 Cre ::ChR2 fl/wt ; NaV1.8 Cre ::DTA fl/wt ; TRPV1 Cre ::DTA fl/wt ; RAMP1 -/-CD8 T cells) and pharmacological (CGRP, BIBN4096, CGRP8-37, capsaicin, QX-314, BoNT/A) approaches used here are specific for nociceptors 22,29,31,32,[39][40][41][53][54][55][56][57][58][59][60][61] . Thus, BoNT/A, QX-314, and BIBN4096 did not impact either B16F10 survival or CD8 + T-cell function in vitro (Supp.…”
Section: Or Other Ethical Endpoints)mentioning
confidence: 99%
“…Optogenetic activation of skin nociceptor neurons mediate an anticipatory immunity against microbes 39 , and by triggering the antidromic release of peptides, potentiates skin 40 and lung 41 immunity. We used transdermal illumination (3.5 ms, 10Hz, 478nm, 100 mW, delivering ~2-6 mW/mm 2 to a 0.39 NA fiber placed 5-10 mm from the skin, for 20 min) to stimulate tumor-innervating NaV1.8 + neurons optogenetically NaV1.8 Cre ::ChR2 fl/wt mice.…”
mentioning
confidence: 99%
“…Possible applications would include bidirectional modulations of neural activities by leveraging electrophysiological or neurotransmitter signals for medications of seizures or Parkinson's disease27,61, 62 . Besides central nervous systems, peripheral neural circuits can also be targeted for medical treatments63,64 . In summary, the results presentedhere provide a viable means for fundamental neuroscience studies and advanced Prigge M, Beyriere F, Tsunoda SP, Mattis J, Yizhar O, et al Red-shifted optogenetic excitation: a tool for fast neural control derived from Volvox carteri.…”
mentioning
confidence: 99%